Effects of a 10-day high-intensity interval training mesocycle on physical performance in male judo athletes - Jokinen, J. (2020)
Judo is an Olympic combat sport where the competition emphasizes several consecutive 20-30 seconds high-intensity efforts interspersed by short recovery periods. High-intensity block training has been found to be an efficient way to develop physical performance, wherein shorter training periods are focused on developing one or two chosen physical abilities. The purpose of this study was to investigate the effects of a 10-day high-intensity interval training period on the performance in male judo athletes. The study included pre and post-tests as well as a 10-day training intervention. The subjects were 19-28 years old men who had competed at least at the Nordic level during the last year (n = 7). The training period included simulated judo matches (4x4 min or intermittent 20-120 s work periods, 85-90%/HRmax) as interval training. In addition, there were technique and tactical training sessions at lighter intensity (50-60% of maximum). Moreover, in strength exercises, maximum strength